Penerapan Metode Suggestopedia Dalam Pembelajaran Mufradāt - Syarofit, Miqdarul Khoir; Wahhab, Abdul; Mahliatussikah, Hanik (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Vocabulary (mufradat) is considered a fundamental element that supports communication, reading, and writing skills in the Arabic language. Research indicates that a good mastery of vocabulary significantly contributes to language learning success. The Suggestopedia method, which utilizes suggestion, music, and a comfortable learning environment, has proven effective in enhancing students' vocabulary acquisition. This method consists of six key elements in its implementation: (1) authority, (2) infantilization, (3) double-plane communication, (4) intonation, (5) rhythm, and (6) pseudo-passivity. Through these elements, the method creates an enjoyable and supportive learning atmosphere. Therefore, we expect its application to positively contribute to Arabic language teaching at the primary and secondary education levels.  This study aims to describe the Suggestopedia method, the meaning and urgency of vocabulary learning, and the implementation of Suggestopedia in vocabulary instruction. The research employs a literature review method by analyzing various books and journal articles relevant to the Suggestopedia method. The findings indicate that (1) Suggestopedia is a method that emphasizes the use of suggestion to create feelings of enjoyment, confidence, and relaxation, enabling both the right and left hemispheres of the brain to function effectively. (2) Mastery of vocabulary is a crucial factor in Arabic language skills, including communication, reading, writing, and text comprehension. (3) There are six key elements to consider in applying the Suggestopedia method for vocabulary instruction: the teacher’s full role, learners as information receivers similar to young children, double-plane communication sources, the use of vocal intonation, musical rhythm, and a calm and comfortable attitude.